Exergame-Driven High-Intensity Interval Training in Untrained Community Dwelling Older Adults: A Formative One Group Quasi- Experimental Feasibility Trial - Rebsamen, Stefanie; Knols, Ruud H.; Pfister, Pierrette Baschung; de Bruin, Eling D. (Frontiers in Physiology, 2019)
Purpose: To investigate the feasibility of an exergame-driven High-Intensity Interval Training (HIIT) and its effects on cardiovascular fitness in untrained community dwelling older adults. Methods: Twelve older participants (ten women, age 72.3 (SD 4.44) years) performed a high-intensity interval exergame intervention three times a week for four weeks. Data was acquired during two baseline and one final measurement. Feasibility outcomes included attrition, adherence, acceptability (Technology Acceptance Model Questionnaire, TAM), perceived usefulness (System Usability Scale, SUS), enjoyment of exergaming and comparisons between actual and target values of training intensity and time. The secondary outcome was exercise capacity (heart rate at rest (HRrest)), heart rate variability (HRV), maximum heart rate (HRmax), and maximum workload (W, in watt) evaluated through maximal exercise testing. Results: Eleven participants completed the study (8.3 % attrition) without any adverse events. Adherence to the HIIT intervention was 90.9 percent and participants showed high acceptance of the intervention with TAM scores between 5.8 and 6.7 points. User satisfaction was rated as excellent (SUS total score: 93.5 of 100) and the overall enjoyment of exergaming scored 4.5 of 5 possible points. Total exercise time ranged from 19 to 35 min with a mean of 30.8 (SD 3.6) min. Actual high-intensity exercise time showed consistency with the target exercise time in ninety-eight percent of trainings. Eighty-six percent of high-intensity intervals met the targeted intensity range (>70-90% of HRmax). Thirty-six percent of the recovery periods were completed with a heart rate above the target range of 50-70% of HRmax. Maximum workload (W) during the incremental exercise test post-training increased significantly compared to the baseline measurements one and two (p = .032, effect size r=0.77 and p=0.012, r=0.87). Conclusion: HIIT through exergaming is feasible, safe and shows high usability and acceptance in community dwelling older people. Exergame-driven HIIT had a significant effect on maximum power output on an incremental exercise test. A more extensive exergame intervention period, higher work to recovery ratios as well as a higher-intensity activity should be considered in future projects.